The System Architecture-Function-Outcome Framework for Fostering and Assessing Systems Thinking in First-Year STEM Education and Its Potential Applications in Case-Based Learning - Rea Lavi; Lykke Brogaard Bertel (MDPI AG, 2024)
Systems thinking is crucial for understanding and solving complex problems and is considered an important thinking skill in engineering. Active learning is considered an effective approach for fostering STEM students' systems thinking. However, viable methods for teaching and assessing systems thinking with active learning across STEM disciplines, particularly in first-year undergraduate education, are still under-researched. In this paper, we introduce a research-based framework named System Architecture-Function-Outcome to help first-year STEM instructors both foster and assess students' introductory systems thinking. To conduct an initial evaluation of the framework's suitability in active learning settings, we designed a directed case-based learning assignment with an adapted article and a rubric for assessing 'introductory systems thinking', as defined in the framework. We deployed the assignment among 84 first-year STEM students and successfully tested its inter-rater reliability, with 75-100% inter-rater agreement across all assessment criteria. We discuss the implications of our results on fostering and assessing first-year STEM students' systems thinking, and outline examples for potential applications of the framework, pending further validation, in case-based learning settings of varying degrees of learner autonomy, from lecture-based to problem-based learning.